(3eUMa TQjas ((3eMeO Hf GdLQ Hf CMeO Hf HcQ s)
(3ChdgG (B:s
(3ShQI GdaGJMI GdMeO ddg QH GdYGdejf GdQMef GdQMje s
(3BNQgG (B:s
(3ShQI GdfGS hJeJ cdeGJ QHc UObkG dGeHOd dcdeGJg hgh GdSejY GdYdje s
(3GdbQBf GdcQje bWY cHjQI efgs
(3GdfSNI HgG MhGTs
(3Hg fXGe GdJYbjHIs
(3ShQI GdaGJMI , GdHbQI , GdfSGA , GdeGFOI , GdCfYGe , GdCfaGd ,s
(3hjTJed CjVkG Ydi eLehYI ShQ CNQi efgG GdHbQI HNW eZQHi YOO eSWQJg (B14 s
(3bQf GdfSN (B:s
Keywords: (3GdcJH GdSeGhjIs